Fabrication and performance analysis of ZnO/Ge/porous Si photodetectors for near-infrared detection - Mazin Mohd Qasim Mogdad; Azhar Abdul Rahman; Naser M. Ahmed; Suvindraj Rajamanickam; Munirah A. Almessiere (Heliyon)
This paper reports on the fabrication of zinc oxide (ZnO)/germanium nanoparticles (Ge NPs)/porous silicon (PSi) photodetector for near-infrared (NIR) detection. Ge NPs are synthesized via pulsed laser ablation in liquid (PLAL) followed by spray coating onto the porous Si substrate and subsequent deposition of a ZnO layer. Field emission scanning electron microscopy (FESEM) confirms the presence of Ge NPs, along with the formation of Ge microwires and a mesh-like Ge pattern on the porous Si surface, attributed to Ge NP supersaturation during spray coating. Ge NPs act as a source of photogenerated electrons, transferring them to the ZnO layer. Additionally, the Ge microwire network facilitates barrier-dominated conduction, further contributing to the generation and transfer of photogenerated electrons. The device achieves its best performance at a bias voltage of 6 V under illumination with 805 nm light, a light intensity of 1.44 mW cm2, and a switching frequency of 6.5 Hz and responsivity of 0.16 A W⁻1.